Antioxidant and Anticancer Potential of Raja Bulu Banana Peel and Heart (Musa acuminata Colla (AAB group)) Ethanol Extracts in MCF-7 Cell Lines - Afifah Bambang Sutjiatmo; Wahyu Widowati; Ida Sumiati; Twice Priestu; Seila Arumwardana; Hanna Sari Widya Kusuma; Alya Mardhotillah Azizah (Majalah Obat Tradisional, 2021)
Breast cancer is an uncontrolled cell growth in breast tissue. Surgical treatments of breast cancer can reduce breast aesthetics and chemotherapy can cause severe side effects. It makes the searches for plants as breast anticancer agents intensively carried out. Several studies have shown that banana peels and hearts possess antioxidant and anticancer activity. This study aims to determine the fruit peel and heart of Raja Bulu banana (Musa acuminata Colla (AAB group)), an endemic banana species in Indonesia, potential as antioxidant and anticancer agent in MCF-7 cells. Antioxidant potential was determined by using 2,2-diphenyl-1picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2) scavenging activity assay. Anticancer potential was determined by cytotoxic test using MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium). The results showed that 70% ethanol extract of fruit peel (PBEE) and heart (HBEE) of Raja Bulu banana had median inhibition concentration (IC50) for DPPH scavenging activity at 115.32 µg/mL and 162.52 µg/mL respectively, while for H2O2 scavenging activity at 624.80 µg/mL and 497.13 µg/mL respectively. Anticancer potential was expressed by inhibiting concentration of 50% proliferation (IC50) of MCF-7 cells for PBEE and HBEE were 115.001 µg/mL and 338.469 µg/mL respectively. This study showed that PBEE and HBEE have antioxidant and anticancer.